Estudo do comportamento do equilíbrio líquido-liíquido de sistemas aquosos bifásicos contendo Pluronic L64 ® + água + sais de sódio - Monteiro Junior, Edson Geraldo (2020)
Two-phase aqueous systems consist of two liquid phases in thermodynamic equilibrium. These are systems with potential for application in the replacement and simplification of stages in extraction and purification processes, especially biocomposites. Thus, this work aims to experimentally evaluate the liquid-liquid balance behavior of two-phase aqueous systems consisting of Pluronic L64 ® + water + sodium salts as well as systems containing glucose, varying the pH of the medium and evaluating the effect of temperature on these systems also by comparison with data from the literature. In this study, the following were discussed: variations in Gibbs energy, enthalpy and entropy of mycelization; the Gibbs energy variation of solvation and the effect of ion hydration volumes on the phase separation behavior. The binodal curves were obtained by turbidimetric titration and the compositions of the tie-lines were calculated following the Merchuk methodology. It was observed that sodium sulfate showed a greater phase separation effect, followed by sodium citrate and sodium tartrate. Higher pH values result in smaller biphasic regions, an effect also observed due to the increase in temperature. The partition coefficients showed that there is a greater distribution of polymer and salt between the phases as the electrolyte is added, while the glucose partition coefficient did not change significantly. The variation in Gibbs free energy from micellization indicates that the phase separation in the systems is spontaneous and that at 293.15K the results are related to the Gibbs energy of ion hydration. On the other hand, the results at 278.15K and 298.15K indicate the predominance of the lower partial molar volume of sodium sulfate over the phase separation process. The analysis of the entropy variation of mycelization also indicated that they are exothermic systems and that there was a change in the conformation of the polymer in solution at higher concentrations of salt. The variation in mycelization entropy showed that the systems are more disordered at lower concentrations of salt and that the order added to the system due to the formation of polymeric micelles is higher than the disorder added by the addition of salt. In this context, the present study added new interpretations on the phenomenon of phase separation for the systems studied through an approach based exclusively on thermodynamic parameters.